Development and In vitro Anticancer Evaluation of Self‐Assembled Supramolecular pH Responsive Hydrogels of Carboxymethyl Chitosan and Polyoxometalate. Issue 5 (5th February 2018) - Azizullah,; Al‐Rashida, Mariya; Haider, Ali; Kortz, Ulrich; Joshi, Sachin A.; Iqbal, Jamshed
Abstract: Self‐assembled supramolecular pH‐responsive hydrogels of carboxymethyl chitosan (CMCh) and the trilacunary heteropolytungstate salt Na12 [α‐P2 W15 O56 ].24H2 O generating the free polyanionP2 W15 in solution, have been synthesized via electrostatic interactions. Benzoyl peroxide (BPO) was used as initiator for grafting poly (methacrylic acid) on polymer skeleton. The developed transparent hydrogels were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X‐ray powder diffraction (XRD) and thermal analysis including thermogravimetric analyses and differential scanning calorimetry (TGA/DSC) and the results confirmed the successful hydrogel formation. The dynamic swelling index and the controlled release pattern of the prepared hydrogels were evaluated at pH 1.2 and 7.4. The maximum swelling index and polyanion release were observed at pH 7.4. Different mathematical models including first order, zero order, Korsmeyer‐Peppas model and Higuchi model were applied and suggested that the release of encapsulatedP2 W15 follows the super case transport‐II mechanism and zero order kinetics. An evaluation of the anticancer activity and cytotoxicity profiling showed that both encapsulatedP2 W15 (hydrogel) and freeP2 W15 possessed a good, dose‐dependent anticancer activity against MCF‐7 and Hela cells, with only minimal cytotoxic effects on normal cells (Vero). Abstract : Main Results Paragraph: Supramolecular self‐assembled pH responsive hydrogels of carboxymethyl chitosan and Wells‐Dawson type trilacunary 15tungsto‐2‐phosphate[α‐P2 W15 O56 ] 12‐ (P2 W15 ) were prepared through electrostatic interactions characterized by different analytical techniques confirming the successful hydrogel formation. Maximum swelling and polyanion release was observed at pH 7.4, with minimum swelling and polyanion release at pH 1.2. Both free polyanion as well as encapsulated polyanion showed a dose dependent anticancer potential against both HeLa and MCF‐7 cells, whereas the polyanion was more efficient against normal Vero cells than doxorubicin.